2018
DOI: 10.1172/jci99986
|View full text |Cite
|
Sign up to set email alerts
|

Regularizing firing patterns of rat subthalamic neurons ameliorates parkinsonian motor deficits

Abstract: The subthalamic nucleus (STN) is an effective therapeutic target for deep brain stimulation (DBS) for Parkinson's disease (PD), and histamine levels are elevated in the basal ganglia in PD patients. However, the effect of endogenous histaminergic modulation on STN neuronal activities and the neuronal mechanism underlying STN-DBS are unknown. Here, we report that STN neuronal firing patterns are more crucial than firing rates for motor control. Histamine excited STN neurons, but paradoxically ameliorated parkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 65 publications
3
47
0
Order By: Relevance
“…Conversely, our data predict that changes in any individual parameter would be sufficient to transition the SNr out of the severe pathological state and into the moderate pathophysiological state, where few if any motor deficits are observed. This prediction is supported by findings that Levodopa (L-DOPA) restores movement predominantly through effects on firing rates (Aristieta et al, 2016; Hernandez et al, 2013; Parker et al, 2018; Ryan et al, 2018) whereas DBS restores movement predominantly through effects on firing patterns (Birdno and Grill, 2008; McCairn and Turner, 2009; McCairn et al, 2015; Zhuang et al, 2018). We note, however, that the therapeutic mechanisms of these treatments remain an open question and could involve changes in both parameters.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Conversely, our data predict that changes in any individual parameter would be sufficient to transition the SNr out of the severe pathological state and into the moderate pathophysiological state, where few if any motor deficits are observed. This prediction is supported by findings that Levodopa (L-DOPA) restores movement predominantly through effects on firing rates (Aristieta et al, 2016; Hernandez et al, 2013; Parker et al, 2018; Ryan et al, 2018) whereas DBS restores movement predominantly through effects on firing patterns (Birdno and Grill, 2008; McCairn and Turner, 2009; McCairn et al, 2015; Zhuang et al, 2018). We note, however, that the therapeutic mechanisms of these treatments remain an open question and could involve changes in both parameters.…”
Section: Discussionmentioning
confidence: 77%
“…This transition appeared to be driven by increased synchrony and correlated strongly with the onset of motor symptoms (Figure 7D–F). This result suggests a mechanism to account for a long-standing paradox of parkinsonian motor symptoms: alleviation of motor symptoms can be correlated with individual physiological parameters (Hammond et al, 2007b; Kravitz et al, 2013; Kühn et al, 2006; Mastro et al, 2017a; Zhuang et al, 2018), but rarely do single parameters predict the onset of motor symptoms (Muralidharan et al, 2016; Nelson and Kreitzer, 2014; Sanders et al, 2013). Our model reconciles this apparent paradox by predicting that motor symptoms emerge when the SNr is in the severe pathological state, which requires alignment of pathophysiology across many different parameters.…”
Section: Discussionmentioning
confidence: 97%
“…The reciprocally connected GPe-STN network has been suggested to be a generator of pathologically correlated cortico-basal ganglia-thalamocortical activity in PD (Moran et al 2011;Tachibana et al 2011;Shouno et al 2017). Indeed, lesion (Bergman et al 1990), electrical stimulation (Benabid et al 2009;Wichmann et al 2018), pharmacological (Levy et al 2001;Tachibana et al 2011), optogenetic (Yoon et al 2014;Mastro et al 2017), genetic (Chu et al 2017;Zhuang et al 2018), and chemogenetic (Assaf & Schiller, 2019;McIver et al 2019) manipulation of the GPe and/or STN have demonstrated that disrupting their pathological activity can ameliorate motor dysfunction in PD and its models. Interestingly, we found that optogenetic inhibition of STN activity facilitated rather than ameliorated abnormal antiphasic GPe neuron activity during cortical SWA, arguing that STN-GPe transmission opposed the abnormal patterning of the GPe by indirect pathway D2-SPNs in dopamine-depleted mice.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, manipulations that oppose the patterning of GPe (and STN) neurons by D2-SPNs, e.g. optogenetic activation of PV GPe neurons (Mastro et al 2017), chemogenetic activation of the GPe (Assaf & Schiller, 2019), and chemogenetic and genetic manipulation of the STN (Chu et al 2017;Zhuang et al 2018;McIver et al 2019) ameliorate motor dysfunction in PD models.…”
Section: Discussionmentioning
confidence: 99%
“…Early hypotheses suggested that high-frequency DBS mimics lesioning by inhibiting neuronal firing from the stimulated structure [4][5][6][7][8] . Others proposed that DBS therapy overrides the pathological burst-type firings with its stimulus-induced regular (tonic) pattern and thereby ameliorated Parkinsonian symptoms [9][10][11] . This effect is not only in the stimulated structure but also travels downstream to the basal ganglia-thalamo-cortical circuit 10,12 and creates an "informational lesion" preventing the relay of pathological firing and oscillations 13 .…”
Section: Introductionmentioning
confidence: 99%